The Effects of Pronunciation Mastery and Critical Thinking Towards EFL Students’ Speaking Skill at IPB Cirebon - Fedro Iswandi; Dwi Nopiyadi (Al-Makki Publisher, 2023)
This is a survey research that was conducted to get empirical data and analyze the effects of pronunciation mastery and critical thinking towards EFL students’ speaking skill at IPB Cirebon. It means there are two independent variables and one dependent variable; variable X1 as the first independent variable (pronunciation mastery) and variable X2 as the second independent variable (critical thinking) which have interconnected and influenced the variable Y as the dependant variable (EFL students’ speaking skill). This research employed a correlational technique that was done through multiple regression analysis. In processing the data, the SPSS program version 21 was applied to describe the data, to conduct the normality, linearity and homogeneity tests, and to test the hypothesis. Data collecting techniques were done through library and field researches. The library research was from theses of other researchers, reference books, dictionaries, articles, journals, and websites. The field research was done at IPB Cirebon by using questionnaire of pronunciation mastery (20 items), critical thinking (20 items), and speaking skill test (10 items). The results of the study identified that 1) there are any significant effects of pronunciation mastery and critical thinking jointly towards EFL students’ speaking skill that is proved by the value of Sig.= 0.000 and Fobserved = 16.147 > Ftable = 3.10). 2) There is a significant effect of pronunciation mastery towards EFL students’ speaking skill that is proved by the value of Sig.= 0.019 and tobserved = 2.394 > Ttable = 1.98). 3) There is a significant effect of critical thinking towards EFL students’ speaking skill that is proved by the value of Sig. = 0.000 and tobserved = 5.068 > ttable = 1.98).